2022
DOI: 10.1128/msystems.00563-22
|View full text |Cite|
|
Sign up to set email alerts
|

Transcriptomic-Guided Phosphonate Utilization Analysis Unveils Evidence of Clathrin-Mediated Endocytosis and Phospholipid Synthesis in the Model Diatom, Phaeodactylum tricornutum

Abstract: Phosphonates contribute ~25% of total dissolved organic phosphorus in the ocean, and are found to be important for marine phosphorus biogeochemical cycle. As a type of biogenic phosphonate produced by microorganisms, 2-aminoethylphosphonic acid (2-AEP) widely exists in the ocean.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 81 publications
1
7
0
Order By: Relevance
“…The other organic matters can also be an alternative nutrient supply, especially for mixotrophic dinoflagellates which is able to digest the intact cell of the prey (Zhang et al, 2011; Jeong et al, 2021;). Our previous work revealed clathrin-mediated endocytosis in the uptake and utilization of DOP by Phaeodactylum tricornutum (Shu et al, 2022), and this mechanism was also recently reported in Symbiodiniacean species (Dinophyta) (Li et al, 2023). Besides organic nitrogen and phosphorus, dissolved metal ions (such as bioactive iron and copper), vitamins, and growth-promoting factors are accessible to dinoflagellates as well (Laglera and Berg, 2009; wells et al, 2015; Amin et al, 2015; Seymour et al, 2017).…”
Section: Discussionsupporting
confidence: 73%
“…The other organic matters can also be an alternative nutrient supply, especially for mixotrophic dinoflagellates which is able to digest the intact cell of the prey (Zhang et al, 2011; Jeong et al, 2021;). Our previous work revealed clathrin-mediated endocytosis in the uptake and utilization of DOP by Phaeodactylum tricornutum (Shu et al, 2022), and this mechanism was also recently reported in Symbiodiniacean species (Dinophyta) (Li et al, 2023). Besides organic nitrogen and phosphorus, dissolved metal ions (such as bioactive iron and copper), vitamins, and growth-promoting factors are accessible to dinoflagellates as well (Laglera and Berg, 2009; wells et al, 2015; Amin et al, 2015; Seymour et al, 2017).…”
Section: Discussionsupporting
confidence: 73%
“…In C. goreaui , the clathrin‐mediated endocytosis was upregulated during PA utilization (Figure 5b). Recently, clathrin‐mediated endocytosis has been reported to perform the phosphonate uptake in the diatom P. tricornutum (Shu et al, 2022), suggesting that endocytosis might also be employed to transport PA into C. goreaui cells. Given that endocytosis has an energy cost, the upregulation of glycolysis and TCA cycle in the PA‐grown cells might provide the energy needed (Figure 4a).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is interesting to find that the phagosome pathway was downregulated in both the ATP and G6P groups in our study (Figure 5). Recently, P. tricornutum was reported to be able to utilize 2-aminoethylphosphonate as the sole source of P (Shu et al, 2022). Transcriptomic analysis in that study indicated that the phagosome pathway (specifically, clathrin-mediated endocytosis) was upregulated, suggesting that this phosphonate might be taken up by this alga via endocytosis.…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, P. tricornutum is a good model species for studying the molecular mechanism of DOP utilization in diatoms. Recently, the bioavailability and utilization mechanisms of phytic acid and 2aminoethylphosphonate have been conducted successively in P. tricornutum (Li et al, 2022;Shu et al, 2022).…”
Section: Introductionmentioning
confidence: 99%